Ways to develop the quality of students’ knowledge by using research methods (Journal of Educational Sciences, 2021)
Тhe purpose of our research work is: to consider ways to improve students ‘communicative compe- tence during the educational process, including identifying methods that affect the formation of students’ communicative competence. The study was conducted in the secondary school-Lyceum No. 143 named after Suyunbai. The study was attended by 97 students, including: 21-students of «6» a class; 50-students of 7 «b» and «с» classes; 26-students of 8 «b» class. The study was conducted using two training methods:1 – the traditional way of learning;2 – experimental, including research methods.Research objectives: determining the level of communicative competence of students; using re-search tasks in the learning process: setting problem questions, monitoring solutions to problem situa- tions; improving their level of communication by providing group work and conducting final calcula- tions.The results of this work showed positive results. As a result of the use of research approaches, logi- cal tasks, laboratory work and role-playing games, the activity of students increased, as well as the level of communication significantly improved. Many pedagogical technologies implemented in the learning process, currently used, are aimed at revealing the individual abilities of students, as well as improving their knowledge, skills, and abilities. I also used cutting-edge technologies and developmental tasks in my research work.Key words: competence, communicative competence, experiment, methodology, interactive meth- od, interpersonal communication.